Identifikasi Nilai Karakter Religius dalam Video Karya Youtuber Millenial - Nur Syamsi (Institut Agama Islam Negeri (IAIN) Samarinda, 2020)
The YouTube page is the most favorite page for millennials. Although the main purpose of the content in the videos is to entertain, but unconsciously it is also able to influence the audience both cognitive, affective, and behavioral. Therefore, it is necessary to identify whether in the video content there are religious characters that can have a positive impact on the audience. This research aims to identify the character of religious values in videos by millennial YouTuber. Data collection method used is the documentation method, data were analyzed using descriptive qualitative content analysis techniques. The results showed that from the entire video uploaded on Ria Ricis Official, Atta Halilintar, and Rans Entertainment YouTube, there were 131 video contents those were used as analysis material. Based on the video analyzed, religious values are obtained which include the values of faith, Islam, ihsan, science, and charity.